VD_FINDINFO HC / 2021 / 627 vom 8. September 2021 - VD Tribunal cantonal (2021)
ÉGALITÉ ENTRE HOMME ET FEMME, GROSSESSE, MATERNITÉ, CONTRAT DE TRAVAIL, RÉSILIATION, MOTIF, VACANCES | 329c CO, 41 CO, 3 LEg, 5 LEg, 6 LEg, 1 LJT